2008
DOI: 10.1007/s00125-008-1061-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between ultraviolet B irradiance, vitamin D status and incidence rates of type 1 diabetes in 51 regions worldwide

Abstract: Aims/hypothesis This study is an analysis of the relationship between ultraviolet B (UVB) irradiance, the primary source of circulating vitamin D in humans, and age-standardised incidence rates of type 1 diabetes mellitus in children, according to region of the world. Methods The association of UVB irradiance adjusted for cloud cover to incidence rates of type 1 diabetes in children aged <14 years during 1990-1994 in 51 regions worldwide was assessed using multiple regression. Incidence data were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
176
0
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(194 citation statements)
references
References 42 publications
10
176
0
8
Order By: Relevance
“…The overall annual incidence rate in the US population is approximately 13 per 100,000 [2], similar to the rate of 12 per 100,000 personyears in US military service members [3]. Annual agestandardised incidence rates of type 1 diabetes vary from a low in the tropics of 0.5 per 100,000 (in Venezuela, latitude 9°N) to a high of 60 per 100,000 in Finland (60°N) [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall annual incidence rate in the US population is approximately 13 per 100,000 [2], similar to the rate of 12 per 100,000 personyears in US military service members [3]. Annual agestandardised incidence rates of type 1 diabetes vary from a low in the tropics of 0.5 per 100,000 (in Venezuela, latitude 9°N) to a high of 60 per 100,000 in Finland (60°N) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…An association has been proposed between vitamin D deficiency and higher risk of type 1 diabetes [5][6][7]. The EURO-DIAB case-control study reported that children who did not receive a vitamin D supplement during infancy had 1.5 times the risk of type 1 diabetes as those who received a vitamin D supplement [7].…”
Section: Introductionmentioning
confidence: 99%
“…lesser donor egg IVF success rates at centers along the North East and improving LBR's at clinics located towards the West (as reflected by increasing zip code numbers) is reminiscent of associations previously described for disorders that have been related to insufficient UVB exposure [12,13] [ [27][28][29][30][31][32][33][34][35]. Directionality of our observations is consistent with trends noted for breast cancer; the prevalence and mortality from breast cancer in North America is reportedly higher in the North East compared to the West, and lower UVB intensity exposure in the North East is a suggested mechanism for this differential [29,30] [ [32][33][34]. Our primary hypothesis was based on a differential in UVB exposure across the regions; indeed, fresh ET related live birth rates were lower in regions with lesser summertime solar UVB indices, and regional midyear UVB intensity was identified as an independent predictor of increasing fresh ET related LBR's (from lowest to highest tertile, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data suggest a relationship between geographical location of birth and residence in areas of low ultraviolet B (UVB) exposure with a spectrum of diseases including multiple sclerosis, type I diabetes and cancers [27][28][29][30][31][32][33][34][35]. Data from the U.S. identify prevalence of most types of cancer, dental caries, and of autism to more closely linked to summertime solar UVB; prevalence of multiple sclerosis in contrast has been related to wintertime UVB and latitude [36].…”
Section: Introductionmentioning
confidence: 99%
“…Some diseases such as type 1 diabetes, multiple sclerosis, high blood pressure and infectious diseases, among others, may be related to less than optimal levels of vitamin D [5]. Obtaining vitamin D production from the sun is thus extremely important.…”
Section: Introductionmentioning
confidence: 99%